2014
DOI: 10.3989/revmetalm.004
|View full text |Cite
|
Sign up to set email alerts
|

Review of thermal analysis applications in aluminium casting plants

Abstract: SUMMARY:Thermal analysis has been applied as a quality control tool in aluminium casting plants for many years. Recently, it has been recognized that the cooling curve and its first derivative analysis offer parameters that can successfully be used in simulation software programs to improve simulation accuracy. The latest developments in cooling curve analysis are related to the application of higher order derivatives, showing that the thermal analysis technique can be applied to calculate the total amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…While this approach is novel it still requires further development to account for various alloy chemistries as well as solidification rate conditions. [37,38] Liquidus temperature determination was not discussed in depth within this work, but it has been demonstrated that application of neutron diffraction brings additional insight on Si atoms clustering in the liquid that most likely took place few degrees above liquidus temperature. [23][24][25] Since quantification of individual phases, i.e., Si and Al during alloy solidification can't be determined accurately by thermal analysis (except by application of quenching experiments), neutron diffraction analysis can help at least partially.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this approach is novel it still requires further development to account for various alloy chemistries as well as solidification rate conditions. [37,38] Liquidus temperature determination was not discussed in depth within this work, but it has been demonstrated that application of neutron diffraction brings additional insight on Si atoms clustering in the liquid that most likely took place few degrees above liquidus temperature. [23][24][25] Since quantification of individual phases, i.e., Si and Al during alloy solidification can't be determined accurately by thermal analysis (except by application of quenching experiments), neutron diffraction analysis can help at least partially.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This approach, which was not used in this study, was demonstrated by Mackay et al [36] for a-Al dendrite and Al-Si eutectic growth analysis in hypoeutectic Al-Si alloys. As far as quantification of phases is concerned, studies have been performed [37,38] where the cooling curve analysis was applied to calculate the total amounts of Cu and Mg based phases that precipitated at the final stages of the solidification process. The total area percentage of the Cu-Mg enriched phases was defined as the ratio of the area between the first derivative of the cooling curve and the hypothetical solidification path of the Al-Si-Cu eutectic to the total area between the first derivative of the cooling curve and the base line.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…LabView software recorded changes in alloy temperature over time in a file. Based on the exact values of temperatures and time, specific values of temperatures for individual structural components of all observed alloys were determined [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to have a fine scale grain size, the most widely practiced method is to present effective nuclei in the liquid metal using Al-Ti-B grain refiners, which usually contain active seeds such as Al 3 Ti, TiB 2 , AlB 2 , or (Al,Ti)B 2 . Thermodynamic studies suggest that these latter particles convert to TiB 2 , so that the titanium diffuses into the (Al,Ti)B 2 particles while the aluminum diffuses out, resulting in the formation of TiB 2 [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%